2022
DOI: 10.3390/su14031169
|View full text |Cite
|
Sign up to set email alerts
|

Day-Ahead DSM-Integrated Hybrid-Power-Management-Incorporated CEED of Solar Thermal/Wind/Wave/BESS System Using HFPSO

Abstract: This paper presents a day-ahead demand-side management (DSM)-integrated hybrid power management algorithm (PMA) with an objective of combined economic and emission load dispatch (CEED) considering losses. The algorithm was tested on an IEEE 30-bus six-generator system consisting of solar thermal/wind/wave/battery energy storage systems (BESSs) considering real-time data of the Gujarat (19°07′ N, 72°51′ E) coastal region and diverse renewable energy (RES) and storage sources. A maiden attempt of utilizing hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…The proposed energy management controller delivered better daily advantages and maximized consumer benefits in energy utilization and cost, with the potential for long-term projections and further optimization algorithms. Kothalanka Kameswara Pavan Kumar et al introduced a unique hybrid power management algorithm (PMA) that integrated DSM to optimize economic and emission load dispatch while taking losses into account [29]. The technique decreased thermal energy consumption and emissions on an IEEE 30-bus system with renewables and storage by using a hybrid firefly particle swarm optimization (HFPSO) approach.…”
Section: Literature Review On Peak Load Management In Indiamentioning
confidence: 99%
“…The proposed energy management controller delivered better daily advantages and maximized consumer benefits in energy utilization and cost, with the potential for long-term projections and further optimization algorithms. Kothalanka Kameswara Pavan Kumar et al introduced a unique hybrid power management algorithm (PMA) that integrated DSM to optimize economic and emission load dispatch while taking losses into account [29]. The technique decreased thermal energy consumption and emissions on an IEEE 30-bus system with renewables and storage by using a hybrid firefly particle swarm optimization (HFPSO) approach.…”
Section: Literature Review On Peak Load Management In Indiamentioning
confidence: 99%
“…BBO base optimization studies are reported in [29][30][31]. The authors in in [32][33][34][35] have employed the PSO technique for controller gain tuning. The authors in [36,37] have used the ABC.…”
Section: Related Workmentioning
confidence: 99%
“…It is thought that multiple generations from different sources, especially with the temporal overlap of wind and waves, will reduce intermittent generation and therefore accelerate energy transmission. Kumar et al [24] examined integrated renewable energy sources such as wave, wind, solar, and battery energy storage systems. They introduced a hybrid power management algorithm (PMA) integrated with day-ahead demand-side management (DSM), aiming at combining economic and emission load distribution (CEED) to reduce losses.…”
Section: Introductionmentioning
confidence: 99%